2001
DOI: 10.1007/s004420100641
|View full text |Cite
|
Sign up to set email alerts
|

The effects of food level and conspecific density on biting and cannibalism in larval long-toed salamanders, Ambystoma macrodactylum

Abstract: Previous studies have examined abiotic and biotic factors that facilitate agonistic behavior. For larval amphibians, food availability and conspecific density have been suggested as important factors influencing intraspecific aggression and cannibalism. In this study, we examined the separate and combined effects of food availability and density on the agonistic behavior and life history of larval long-toed salamanders, Ambystoma macrodactylum. We designed a 2×2 factorial experiment in which larvae were raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 54 publications
4
77
0
Order By: Relevance
“…Comparative data suggest that species with age-structured populations typically have higher thresholds (e.g., 55% to .140% for piscivorous fishes; Popova 1967, Claesson et al 2004, Persson et al 2006) than those in which size structure occurs mainly within generations (e.g., 20-30% for dragonflies, Wissinger 1992; 40% for caddisflies, Greig and Wissinger 2010; ,40% for terrestrial invertebrates, Polis 1981). Although cannibalism within cohorts of ambystomatid salamanders is commonplace and facilitated by the development of size structure, size thresholds have not been reported (e.g., Polis and Myers 1985, Petranka 1989, Van Buskirk and Smith 1991, Crump 1992, Maret and Collins 1997, Hoffman and Pfennig 1999, Ziemba and Collins 1999, Wildy et al 2001. In our study, we found that cannibalism between different year classes of tiger salamanders only occurred between individuals that differed by .50% in body size (Fig.…”
Section: Measuring Ecologically Relevant Cannibalism Size Thresholdsmentioning
confidence: 99%
“…Comparative data suggest that species with age-structured populations typically have higher thresholds (e.g., 55% to .140% for piscivorous fishes; Popova 1967, Claesson et al 2004, Persson et al 2006) than those in which size structure occurs mainly within generations (e.g., 20-30% for dragonflies, Wissinger 1992; 40% for caddisflies, Greig and Wissinger 2010; ,40% for terrestrial invertebrates, Polis 1981). Although cannibalism within cohorts of ambystomatid salamanders is commonplace and facilitated by the development of size structure, size thresholds have not been reported (e.g., Polis and Myers 1985, Petranka 1989, Van Buskirk and Smith 1991, Crump 1992, Maret and Collins 1997, Hoffman and Pfennig 1999, Ziemba and Collins 1999, Wildy et al 2001. In our study, we found that cannibalism between different year classes of tiger salamanders only occurred between individuals that differed by .50% in body size (Fig.…”
Section: Measuring Ecologically Relevant Cannibalism Size Thresholdsmentioning
confidence: 99%
“…Food restriction generates substantial morphological and developmental plasticity among anuran (Wilbur and Collins, 1973;Werner and Anholt, 1996;Kupferberg, 1997) and urodele (Wildy et al, 2001;Rohr et al, 2004) larvae. Generally, studies have shown that food restriction causes reduced body sizes at metamorphosis, but the effects on development time vary depending on when the restriction is experienced.…”
Section: Introductionmentioning
confidence: 99%
“…Overlaying the effects of a changing environment is the influence of the population on its own survival rates. Densityrelated reduction in survival rates has been attributed to increased competition (De Leo and Gatto 1996), displacement into marginal habitats (Frederiksen and Bregnballe 2000), and increased agonistic interactions (Wildy et al 2001). Population survival rates may also be affected as the population structure changes owing to shifting sex ratios or the ad-vent of strong age-classes owing to sex-or age-specific mortality rates.…”
Section: Introductionmentioning
confidence: 99%